Les liants organiques présents dans les polychromies d’objets ethnographiques - Vinciane Bruttin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This study concentrates on different kinds of binding media present on ethnographic artefacts from central Africa. Once the preliminary examination and documentation of the painted parts were finished the analyses of selected samples by Fourier Transform Infrared Spectroscopy (FT-IR) revealed  variable ratios of binding media. Their  compositions were specified by using Gas Chromatography-Mass Spectrometry (GCMS) and Direct Temperature-Resolved  Mass Spectrometry (DTMS).